«Ti muova il pianto che dai lumi io verso». Epic Models in Fortunata Sulgher Fantastici (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
The essay aims to investigate the models, the sources and the forms of the poetic work of Fortunata Sulgher Fantastici, known by the Arcadian name of Temira Parasside. After tracing the outlines of the cultural framework in which the acclaimed improviser fits, here is provided a review of the Homeric and Virgilian texts included in Temira Parraside’s Componimenti poetici of 1785, then republished as Poesie in 1794. The paper also carries out the analysis of the poems: the characters of Andromache, Briseis, Achilles, Penelope and Dido bring out a pattern of returns to the past resulting from a wise and interlaced use of the models, that make Sulgher’s lyrical discourse perfectly consistent with the culture of her time.
Keywords: Florence; Fortunata Sulgher Fantastici; Epic Poetry; Extemporaneous poetry; Eighteenth-century; Controversy of Ancient and Modern; Homer; Andromache; Achilles; Dido; Briseis; Penelope; Arcadia Academy